Size Perusahaan dan Profitabilitas: Kajian Empiris Terhadap Perusahaan Manufaktur yang Terdaftar di Bursa Efek Jakarta - Hadri Kusuma (Economic Journal of Emerging Markets, 2005)
This research examines the relationship between profitability and size of manufac¬turing companies for the period of 2000 to 2003. Two measures of profitability are em¬ployed: Earnings before interest, taxes, depreciation and amortization (EBITDA margin); and earnings before interest and taxes (EBIT margin). The measure of firm size is the num¬ber of employees. The results are consistent with theories of firm size that specify trade-offs between economies of scale and organizational costs and with theories that ascribe certain competencies to firms that allow them to offset the advantages often ascribed to large firms such as economies of scale.Key Words:    Size, Profitabily, Economy of Scale, Organisational, Competency, and Critical resources